2021
DOI: 10.1155/2021/5570229
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Has a Protective Role against Osteoporosis in Ovariectomized Rats

Abstract: The reduction in estrogen levels results in a decrease in bone density at menopause. Irisin is a myokine that modulates the benefits of exercise, which may include bone health. This study was planned to examine irisin’s impact in preventing osteoporosis after ovariectomy. 4 groups of female albino rats (10 rats/group): control, sham-operated, ovariectomized (OVX-control), and OVX-irisin-treated. Serum levels of bone markers [osteocalcin (OC), bone alkaline phosphatase (BALP), tartrate-resistant acid phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 64 publications
(73 reference statements)
5
21
0
Order By: Relevance
“…Histomorphometric analysis also showed that r-irisin increased the number of osteoblasts and decreased the number of osteoclasts. This result is consistent with the results in the deovulated rat model (Morgan et al, 2021). Irisin protected normal bone structure, maintained bone density, and maintained bone metabolic homeostasis.…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...supporting
confidence: 92%
“…Histomorphometric analysis also showed that r-irisin increased the number of osteoblasts and decreased the number of osteoclasts. This result is consistent with the results in the deovulated rat model (Morgan et al, 2021). Irisin protected normal bone structure, maintained bone density, and maintained bone metabolic homeostasis.…”
Section: The E Ects Of Irisin On Osteoarthritis Irisin and Bone Miner...supporting
confidence: 92%
“…Expanding evidence has revealed that irisin is involved in various pathophysiological processes including musculoskeletal metabolism, lipid and glucose metabolism, neural regulation, inflammation, and degenerative diseases [17][18][19][20]. Likewise, accumulating studies have shown that irisin plays an essential role against the progression of skeletal degenerative diseases such as osteoporosis and osteoarthritis [21][22][23][24]. Besides, it has been reported that irisin is a powerful regulator of the metabolism of ECM, including upregulating the levels of COL2A1 and ACAN and downregulating the productions of matrixdegrading enzymes in chondrocytes [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In ovariectomized mice, R-irisin prevented trabecular BL and induced greater BMD, while the number of OBs was increased, and the number of OCs was decreased in parallel [ 124 ]. Additionally, R-irisin returns the serum levels of osteocalcin, ALP, and tartrate-resistant acid phosphatase 5b in ovariectomized rats back to the same serum levels as non-ovariectomized rats [ 125 ]. Addition of SCHN to bMSCs had a protective effect on µ g -induced reduction of ALP activity and a promoting effect on the deposition of hydroxyapatite crystals [ 59 ].…”
Section: Discussionmentioning
confidence: 99%